Lécba chronické myeloidní leukémie--ménĕ bĕzný pohled na moderní postupy - Mayer, J; Zácková, D; Klamová, H; Doubek, M (Casopis lekaru ceskych, 2008)
Chronic myeloid leukemia has got an outstanding position among the other oncology diseases, particularly due to specific chromosomal abnormality called Philadelphia chromosome, its molecular consequence BCR/ABL fusion gene and its biologic product BCR/ABL tyrosinekinase, which is responsible for the leukemic transformation of the hematopoetic cells. We can see a real revolution in the treatment of the chronic myeloid leukemia in the last few years. The authors pay attention to the developement of the new drugs in the large historical consequences from the beginning in the 19th century (describing leukemia first time) to the introduction of the new small specific molecules into the clinical practice.
Keywords: Leukemia, Myelogenous, Chronic, BCR-ABL Positive; lidé; chronická myeloidní leukemie; Humans